A READING OF THE CONCEPT OF LONGUE-DUREE CAPITALISM: THE CONTRIBUTIONS OF FERNAND BRAUDEL, IMMANUEL WALLERSTEIN AND GIOVANNI ARRIGHI - Silvano Ferreira, Leonardo Antonio [UNESP]; Zanardi Coltro, Fabio Luiz (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2021)
The aim of this article is to read, from a brief dialogue with the authors, Fernand Braudel, Immanuel Wallerstein and Giovanni Arrighi, on the concept of long-term capitalism. The study consists of demonstrating the conceptual and methodological contributions of these authors, to think and understand the constitution of capitalism in their analyzes of the world-system, which are empirically based. The objective is to understand the characteristics and dynamics of capitalism today, from the perspective of the concept of historical capitalism. To do so, we will go through an analysis of the concept of capitalism dynamics in Fernand Braudel, followed by an understanding of the concept of historical capitalism, according to Immanuel Wallerstein, and, finally, analyzing the perspective of systemic accumulation cycles, according to Giovanni Arrighi.
Keywords: Capitalism; Historical capitalism; Systemic cycles of accumulation; Work